Darwinian evolution of the taxation of trusts: a comparative analysis - Pinto, Dale; Karlinsky, Stewart (CCH Australia Limited/Monash University, 2007)
This article will undertake a comparative analysis of the evolution of trusts in Australia and the United States. While the concept of a trust is well understood in both jurisdictions, it will be shown that the way trusts have been used in a commercial and taxation law context is quite different in the United States as compared with Australia. The article will commence by examining the American and Australian experiences with trusts, including a brief examination of how trusts are used and how many trusts file tax returns. This will provide an important context and backdrop to the ensuing discussion and analysis. In terms of any examination of the evolution of trusts, the British roots to the concept of a trust are important and will be analysed next in the article. Following this, a discussion of trust attributes in the United States will be undertaken. The next part of the article will examine in more detail how and why trusts are used in Australia, focusing specifically on some of the taxation implications of the use of trusts in Australia. A comparative analysis will be undertaken in the United States context, showing how similar tax outcomes can be arrived at without using the technique of a trust. The article will conclude by examining some important tax and public policy implications of the use of trusts in both Australia and the United States.